On the QoS of IPTV and Its Effects on Home Networks - Dongyu Qiu (International Journal of Digital Multimedia Broadcasting)
In Internet Protocol Television (IPTV) systems, Quality-of-Service (QoS) is a critical factor for user satisfaction. In this paper, we first propose a queueing model for IPTV systems and discuss how to ensure the QoS of IPTV. We then use the model to analyze the effects of IPTV traffic on other applications in home networks. We find that TCP congestion control may not work well under this circumstance and propose a new approach to improve the performance of TCP. We also verify our results through ns2 simulations.